Short-term glucocorticoid treatment increases insulin secretion in islets derived from lean mice through multiple pathways and mechanisms. - Hult, M; Ortsäter, H; Schuster, G; Graedler, F; Beckers, J; Adamski, J; Ploner, A; Jörnvall, H; Bergsten, P; Oppermann, U (2009)
Chronic exposure to elevated levels of glucocorticoids leads to metabolic dysfunctions with hyperglycemia and insulin resistance. Long-term treatment with glucocorticoids induces severe impairment of glucose-stimulated insulin secretion. We analyzed the effects of short-, and medium-term (2-120h) treatment with 50-200nM glucocorticoids on primary pancreatic islet cultures derived from lean C57BL/6J mice. In contrast to animal models of insulin resistance, beta-cells from lean mice respond with an increased glucose-stimulated insulin secretion, with a peak effect around 18-24h of treatment. Analyses of the insulin secretion response reveal that early and late phase responses are dissociated upon glucocorticoid treatment. Whereas late phase responses return to basal levels after long treatment, early phase responses remain increased over several days. Increased insulin secretion is also obtained by incubation with the inactive glucocorticoid dehydrocorticosterone, pointing to an important role of the enzyme 11beta-hydroxysteroid dehydrogenase type 1 in mediating glucocorticoid effects in beta-cells. Transcript profiling revealed differential regulation of genes involved in mediation of signal transduction, insulin secretion, stress and inflammatory responses. The results show that short- to medium-term glucocorticoid treatment of pancreatic islets derived from lean mice leads to an increased insulin release and may constitute an important parameter in changing towards a pro-diabetic phenotype.